2016
DOI: 10.18632/oncotarget.11331
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing identifies articular cartilage and subchondral bone miRNAs after ESWT on early osteoarthritis knee

Abstract: Extracorporeal shockwave therapy (ESWT) has shown chondroprotective effects on the initiation of the osteoarthritis (OA) changes of the rat knee. This study evaluated 69 significant expressed profiles of microRNA (miRNA) in the articular cartilage and subchondral bone after ESWT. There were 118 target genes identified for miRNAs of interest in articular cartilage and 214 target genes in subchondral bone by next generation sequencing (NGS). In principal component analysis (PCA), the relationships of miRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…As a new technique, extracorporeal shockwave therapy (ESWT) uses a single-impulse transient acoustic wave induced by pneumatic, electrohydraulic, electromagnetic, or piezoelectric generators which focuse on the area needed to be treated [7]. ESWT has shown an effect on articular cartilage and subchondral bone development, neovascularization, tissue regeneration, and inflammatory response in some animal experiments [8][9][10]. ESWT also succeeds in the treatment of several musculoskeletal diseases, including tennis elbow syndrome, plantar fasciitis, tendon disease, and fracture nonunions, in some clinical studies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As a new technique, extracorporeal shockwave therapy (ESWT) uses a single-impulse transient acoustic wave induced by pneumatic, electrohydraulic, electromagnetic, or piezoelectric generators which focuse on the area needed to be treated [7]. ESWT has shown an effect on articular cartilage and subchondral bone development, neovascularization, tissue regeneration, and inflammatory response in some animal experiments [8][9][10]. ESWT also succeeds in the treatment of several musculoskeletal diseases, including tennis elbow syndrome, plantar fasciitis, tendon disease, and fracture nonunions, in some clinical studies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [15] performed a gene analysis of miRNAs expressed in joint tissues after an application of ESWT, revealing rather conflicting data that do not allow us to reach clear and definitive conclusions regarding the role of ESWT in EKOA.…”
Section: Discussionmentioning
confidence: 99%
“…The chondroprotective role of ESWT was also evaluated by Cheng et al [15], who performed a gene processing of microRNAs (miRs) found in articular cartilage and subchondral bone following ESWT. The authors conducted a preclinical study on 30 rats undergoing ACL resection in combination with MMx (ACLT + MMx) to induce EOA-like changes in joints (OA group).…”
Section: Eswtmentioning
confidence: 99%
“…11 ESWT creates a micro-trauma which induces angiogenesis, [12][13][14][15][16] potentially reducing inflammation and improving the quality of cartilage. 9,[17][18][19][20] It decreases nerve conduction velocity, which could explain the immediate antinociceptive effect. [21][22][23][24] However, the exact mechanism of action on the pain is still uncertain.…”
Section: Introductionmentioning
confidence: 99%